Developing physical fitness through games among the educable mentally retarded children in the primary level - De Leon, Josefina (Arriola) 1939- (University of the Philippines, College of Education, 1973)
Games which may facilitate the development of physical fitness among the educable mentally retarded children in the primary level were presented in this study. It explored specifically the importance of physical fitness to the educable mentally retarded children in the primary level, and important points for a special education teacher to consider in order to function better in their quest to develop the mentally retarted children physically fit individuals.